(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper deals with the review on development of thermo elasticity. It is demonstrated the types of thermo elasticity i.e. uncoupled, coupled and generalised thermo elasticity.The basic equation of two temperature thermo elasticity in context of lord and Shulman theory and Green and Nagdhi theories of generalised thermo elasticity are reviewed. Relevant literature on two temperature thermo elasticity and state space approach is also reviewed.